Properties and microstructure of ultrafine-crystalline BaTiO3-based energy storage ceramics - LIU Bai-bo; WANG Xiao-hui; LI Long-tu (工程科学学报, 2017)
Al2O3, SiO2 and ZnO were coated around nano-sized BaTiO3 particles by means of aqueous chemical coating. Then, BaTiO 3 -based energy storage ceramic material with average grain size of 120 nm was fabricated by the two-step sintering method. The coating layer can restrain grain growth and abnormal grain growth, and can enhance significantly the AC breakdown strength of the material to over 150 kV·cm-1, while providing energy density of 0.829 J·cm-3. Energy-dispersive spectroscopy proves the gathering of doping elements near grain boundaries, thus indicating the existence of a core-shell structure. High-temperature impedance spectroscopy and fitting results further explain that the energy storage properties were improved. Although the energy density of this ultrafinecrystalline ceramic material is moderate, the advantages of fine grains and low sintering temperature make it possible for the material to be used in multilayer ceramic capacitors, which can increase energy storage by orders of magnitude. This improvement is impossible to achieve with conventional energy storage ceramics.